Pelatihan Rumah Ramah Literasi untuk Meningkatkan Keterampilan Stimulasi Literasi pada Orang Tua (Gadjah Mada Journal of Professional Psychology (GamaJPP), 2018)
This research developed a “Rumah Ramah Literasi” training program to improve parent’s stimulation of literacy skills using environmental print as a media. The research hypothesis is the “Rumah Ramah Literacy” training program can improve parent’s stimulation of literacy skills. The experimental design employed in this present study is The Untreated Control Group Design with Pretest and Posttest Sample s. The subject of this research is 18 mothers which are 9 mothers in the experimental group and 9 mother rs in the control group. The data were analyzed using Mann Whitney U-Test. The result of this study was found that gain score literacy stimulation was significantly higher, U(n=18) =0,001, p<0,05 in the experimental group (M=14) than in the control group (M=5).This indicates that “Rumah Ramah Literasi” training program could improve parents’ literacy stimulation. The effect size of “Rumah Ramah Literacy” training program was 0,84.